A Study on Neutrosophic Anti-Fuzzy Subsemiring of a Semiring - Ekambaram, K.R.; Saravanan, V.; Sampathu, J. S. (Journal of Informatics and Mathematical Sciences, 2025)
In this research, we endeavor to explore the algebraic properties of neutrosophic anti-fuzzy subsemirings (NAFSSR) within a semiring (SR), and we present several theorems related to NAFSSR in the context of a semiring (SR).